Using SignalR Library to set up a cluster of IoT devices. (Manning Publications, 2021)
Clustering is an important functionality in the Internet of Things (IoT). It allows multiple devices to act as one and coordinate the work between themselves. If you use .NET for developing distributed IoT applications, you can use a library called SignalR. This library facilitates real-time two-way communication between the client and the server with minimal setup code. So, once the client makes the initial connection request, there is no longer request-response mechanism in place. Messages can travel both ways while the connection is live.